The usage of empty fruit bunch (EFB) and palm pressed fibre (PPF) as substrates for the cultivation of pleurotus ostreatus - Mohd Tabi, Amal Nafissa; Ahmad Zakil, Fathie; Mohd Fauzai, Wan Nur Fauzan; Ali, Noorhalieza; Hassan, Onn (Penerbit UTM Press, 2008)
At present Malaysia is the largest exporter of palm oil in the international market. In the process of extraction of palm oil from oil palm fruit, biomass materials such as palm empty fruit bunch (EFB) and palm pressed fibre (PPF) are generated as waste products. This research was undertaken to evaluate the use of empty fruit bunch (EFB) and shredded palm pressed fibres as the substrates for the cultivation of Pleurotus ostreatus (oyster mushroom) which currently use sawdust of rubber trees. Five different substrates were prepared either alone or in combinations with rubber tree sawdust. These substrates were supplemented with fixed ratio of rice bran and limestone to increase the yield of Pleurotus ostreatus. The highest yield observed is from substrate comprising 50% PPF and 50% rubber tree sawdust with a mean yield of 0.19375 kg. Both shredded palm pressed fibre and empty fruit bunch show potential as substrate for the cultivation of Pleurotus ostreatus.